Chiral VAPOL Imidodiphosphoric Acid-Catalyzed Asymmetric Vinylogous Mannich Reaction for the Synthesis of Butenolides - Zhou, Tianyun; Gao, Jigang; Liu, Guofeng; Guan, Xukai; An, Dong; Zhang, Suoqin; Zhang, Guangliang (Synlett, 2018)
Chiral butenolides were synthesized by the enantioselective vinylogous Mannich reaction. Chiral (VAPOL)-type imidodiphosphoric acids are efficient catalysts for the asymmetric vinylogous Mannich (AVM) reaction of aldimines and trimethylsiloxyfuran in toluene. Under the optimized conditions, a series of butenolides were obtained with high yields (up to 98%) and enantioselectivities (up to 97% ee) as well as excellent diastereoselectivities (up to 99:1 dr).
Keywords: butenolides; trimethylsiloxyfuran; organocatalysis; enantioselectivity; asymmetric vinylogous Mannich reaction